Transdermal Delivery of Bioidentical Progesterone with a Steroid 5α-Reductase Inhibitor (Dutasteride): a Pilot Study - sara Zargar-Shoshtari; Hannaneh Wahhabaghei; Abdolrasoul Mehrsai; Jingyuan Wen; Raid Alany (Frontiers Media S.A., 2011)
Purpose: Bioavailability of transdermal progesterone is low and variable. This may be attributed to transdermal metabolism by the 5α-reductase enzymes or the direct transport to the saliva. The objective of the current study was to evaluate the effect of enzyme inhibition on the bioavailability of transdermal progesterone. Serum and salivary progesterone levels were evaluated to gain a better insight into the mechanism progesterone transport across the skin. Method: Twenty postmenopausal women with a Follicle Stimulating Hormone > 40iu/L were recruited to take part in the study. The subjects were randomly allocated to either dutasteride (n=10) or placebo (n=10). Each group applied either 500mg of non ionic cream or dutasteride cream (2mg/g) to the right arm for 2 weeks. This was followed by applying 500mg of progesterone or progesterone dutasteride cream (equivalent to 40mg of progesterone) for a further 2 weeks. On day 30 blood and saliva were collected for over 12 hours and progesterone concentration was measured. Results: The baseline progesterone concentration on day zero was 0.1 ng/ml. On day 30 baseline progesterone levels increased significantly (p